Answer:
So the correct answer is"none of the above".
Step-by-step explanation:
z+(z+6)=z+z+6=2z+6. \\ \\ (z+z)+(z+6)=z+z+z+6=3z+6. \\ \\ (z+6)+6=z+12 \\ \\
Answer:It’s. B
Step-by-step explanation:
Answer:
111.65
Step-by-step explanation:
$15.25 x 3 = $45.75
$32.95 x 2 = $65.9
Total: $111.65
Answer:
-5x+10
Step-by-step explanation:
-5(x-2)=-5x+10
Xy is the number
A) x + y = 7
B) 10y + x = 10x + y + 9
collecting terms of equation B
B) -9x + 9y = 9
multiplying A) by 9
A) 9x + 9y = 63 then adding it to equation B)
B) -9x + 9y = 9
18y = 72
y = 4
x = 3
The number is 34